2013
DOI: 10.1371/journal.pone.0077067
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor Gene TUSC2 (FUS1) Sensitizes NSCLC to the AKT Inhibitor MK2206 in LKB1-dependent Manner

Abstract: TUSC2-defective gene expression is detected in the majority of lung cancers and is associated with worse overall survival. We analyzed the effects of TUSC2 re-expression on tumor cell sensitivity to the AKT inhibitor, MK2206, and explored their mutual signaling connections, in vitro and in vivo. TUSC2 transient expression in three LKB1-defective non-small cell lung cancer (NSCLC) cell lines combined with MK2206 treatment resulted in increased repression of cell viability and colony formation, and increased apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…Several reports have revealed a critical role for this pathway in a broad range of CD8 + T cells and IL15-induced NK cell proliferation and cytotoxicity. This is compatible with our previous reports that TUSC2 inhibits mTOR signaling in EGFR wildtype NSCLC (2). TUSC2 enhanced IL15/ IL15R, IL18, and Th1, all of which are regulated by mTOR, and perhaps mTOR inhibition by TUSC2 promotes constitutive release of these cytokines and others, therefore promoting enhanced proliferation and activation of NK and CT8 + T cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several reports have revealed a critical role for this pathway in a broad range of CD8 + T cells and IL15-induced NK cell proliferation and cytotoxicity. This is compatible with our previous reports that TUSC2 inhibits mTOR signaling in EGFR wildtype NSCLC (2). TUSC2 enhanced IL15/ IL15R, IL18, and Th1, all of which are regulated by mTOR, and perhaps mTOR inhibition by TUSC2 promotes constitutive release of these cytokines and others, therefore promoting enhanced proliferation and activation of NK and CT8 + T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Researchers reported that NSCLC patients with loss of TUSC2 expression had significantly worse overall survival (OS) than did those with normal TUSC2 expression (1). TUSC2, a mitochondrial protein, is multifactorial in its mechanism of action and is involved in a wide array of cellular processes, including induction of apoptosis, inhibition of many kinases, mitochondrial calcium homeostasis, inhibition of reactive oxygen species (ROS) response, and increase of immune stimulation (2–6). In a previous study, we developed nanovesicles encapsulating an optimized TUSC2 expression plasmid.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on FGFR2 expression because its level was reduced to the greatest extent. In addition, a previous study has highlighted FGFR2 signaling as a mechanism of acquired resistance to EGFR TKIs, and suggested that treatment of NSCLC patients with combinations of EGFR and FGFR specific TKIs may be a strategy to enhance efficacy of single EGFR inhibitors [ 23 ]. We found a significant inhibition of FGFR2 expression by TUSC2 transient transfection alone, suggesting a functional role for TUSC2 in the observed cooperative effect.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation was proposed to sensitize NSCLC cells to erlotinib23. It is worth noting that TUSC2 directly activates AMPK allowing AMPK to drive cell dearth more effectively524.…”
Section: Discussionmentioning
confidence: 99%